William Carlos Williams. - Brinnin, John Malcolm, 1916-1998 (University of Minnesota pamphlets on American writers ;, 1963)
William Carlos Williams - American Writers 24 was first published in 1963. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.